Electrical, thermal and electrochemical properties of SmBa1−xSrxCo2O5+δ cathode materials for intermediate-temperature solid oxide fuel cells. (20th June 2016) - Subardi, Adi; Chen, Ching-Cheng; Cheng, Meng-Hsien; Chang, Wen-Ku; Fu, Yen-Pei
Abstract: The effects of Sr doping on the Ba-site of SmBaCo2 O5+δ in term of structure characteristics, thermal expansion coefficients (TECs), electrical properties and electrochemical performance have been investigated as cathode material for intermediate-temperature solid oxide fuel cells (IT-SOFCs). The TECs of SBSC-based cathodes are calculated from 19.8 − 20.5 × 10 −6 K −1 in the temperature range of 100–800 °C, and the TEC values decrease with increasing Sr content. The oxygen content and the average oxidation state of cobalt increase with increasing Sr content determined by the X-ray photoelectron spectroscopy (XPS) and Thermogravimetry analysis (TGA) results. At a given temperature, the electrical conductivity values are in the order as follows: SBSC55 > SBSC73 > SBSC91. This behavior might be due to the increase in electronic hole. The electrical conductivities of SBSC55 at 600 °C are distributed in the range of 660 S/cm of p (O2 ) = 0.01 atm to 1168 S/cm of p (O2 ) = 0.21 atm, indicating that the cathode can endure reducing atmosphere. SBSC55 with high electrical conductivity in p (O2 ) = 0.01 atm is ascribed to SBSC55 with stable double-perovskite structure at such low oxygen partial pressure. The SBSC55 cathode showed the highest power density of 304 mW/cm 2 at operating temperature of 700 °C. Based on the electrochemical properties, SBSC55 is a potential cathode for IT-SOFCs.